(untitled) (Damu Journal of Sport Sciences, 2025)
The importance of the research emerged in an attempt to attract everything related to the success of this type of shooting, whether at the level of training or at the level of selecting players in terms of their anthropometric measurements, and the corresponding mechanical principles in a manner consistent with the requirements of the game, so the researcher decided to identify the extent of the relationship between anthropometric measurements and some of the kinematic indicators and the extent of their relationship to the accuracy of shooting from the free throw in basketball, and to put the results of this study at the disposal of those in charge of the training process. The research problem is summarized by asking the following question: - What is the relationship between some body measurements and some biokinematic variables of the throwing arm and the accuracy of shooting the free throw in junior basketball? The researcher used the following measurements: Special measurements (arm lengths): included arm length, homers length, forearm length Special measurements (arm circumferences): included homers circumference, forearm circumference. Player-specific indicators at the moment of shooting: included the elbow angle, homers angle for the throwing arm. The researcher also used kinematic variables: Ball-specific indicators at the moment of shooting: included the ball's height point, ball launch angle. The researcher concluded that there is a significant correlation and a high percentage between the body variables of the throwing arm and some biokinematic variables and the accuracy of shooting the free throw.